RANCANGAN DECISION SUPPORT SYSTEMS UNTUK DIVISI PEMBELIAN PT. S - Willy Lautan (Jurnal Administrasi Bisnis, 2020)
ABSTRACTIndonesian people have a variety of hobbies and activities. Today, a hobby that is being cultivated is one of the hobbies related to outdoor activities In carrying out hobbies and outdoor activities, supporting equipment is needed to carry out these activities. Because of this it creates an outdoor business opportunity, one of them is a tactical equipment business. PT. S is one company that sells tactical equipment. PT. S has problems in purchasing procedures, especially in making purchasing decisions. Therefore PT. S requires an information system that is a management control system. The system development process carried out publishes system analysis and system design.The research method used in this study is descriPT.ive analytical. Data analysis techniques use Laudon diagrams, five strength porters, SWOT analysis to analyze external and internal considerations. The Business Challenge Bundle is used to map needs related to the system design needed by PT. S.After determining the system analysis, the system design used by researcher is Business Process Modeling and Notation (BPMN), User Interface, and Decision Tree. Business Process Modeling and Notation (BPMN) to evaluate actual business processes and proposed business process. User interface to help users access information systems. Decision tree to explain the logic of thinking.To be able to make it easier to improve decision making, researcher create user interface findings to form the DSS Dashboard.Keywords : Management control system, Decision support system, information system, porter five forces, SWOT analysis, decision tree, BPMN